(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
Over the past 10 years, research on integrated water security measurement and management has increased rapidly as a result of the effects of water stress, where water scarcity is notorious worldwide. Although water security has been conceptually addressed from different perspectives, it is necessary to understand from different perspectives, it is necessary to understand from different perspectives, it is necessary to understand the dimension of water security markers as they intervene in the rural environment and within this at the scale of family agricultural production, given their importance for the food security and sovereignty of the territories. Therefore, the present work aims to analyze the thematic dimensions of water security frameworks in the scientific dissemination in order to evaluate the conceptual, methodological and operational integration in the existing frameworks. To this end, a systematic review of the Scopus database was carried out using the VosViewer and CiteSpace applications. Detailed analysis of 195 relevant documents. The results show that 37 has been used to design the existing security framework. Although in the aspects of family agricultural production were mentioned in the 12% of the articles, the direct impacts in this area have been little considered, taking into account weaknesses in the management of the physical infrastructure and its impact on those family farming.